Evaluation of U.S. Air Force preacquisition technology development (National Academies Press, 2011)
From the days of biplanes and open cockpits, the air forces of the United States have relied on the mastery of technology. From design to operation, a project can stretch to 20 years and more, with continuous increases in cost. Much of the delay and cost growth afflicting modern United States Air Force (USAF) programs is rooted in the incorporation of advanced technology into major systems acquisition. Leaders in the Air Force responsible for science and technology and acquisition are trying to determine the optimal way to utilize existing policies, processes, and resources to properly document and execute pre-program of record technology development efforts, including opportunities to facilitate the rapid acquisition of revolutionary capabilities and the more deliberate acquisition of evolutionary capabilities. This book responds to this need with an examination of the current state of Air Force technology development and the environment in which technology is acquired. The book considers best practices from both government and industry to distill appropriate recommendations that can be implemented within the USAF.